Rarely b-continuous functions - (:unkn) unknown (My University, 2013)
In this paper we introduce a new class of functions called rarely b-continuous. Some characterizations and several properties concerning rare b-continuity are obtained.
Keywords: B-open; Rare set; Rarely almost compact; Rarely b-continuous